The significance of genetic and molecular investigations in porphyria cutanea tarda - Kowalska, Maria; Kowalik, Artur (Dermatology Review/Przegląd Dermatologiczny, 2012)
Porphyria cutanea tarda (PCT) is a chronic metabolic disease and its clinical picture and methods of treatment are well known. The rapid development of genetic and molecular investigations enables one to establish early diagnosis, precise type of PCT, detection of such complications as hepatic cirrhosis or hepatic carcinoma and introduction of prophylactic actions. Mutations in the UROD gene are highlighted in familial type of PCT with a possibility to detect persons with latent disease. Appropriate prophylactic procedures may prevent the development of overt disease. The haemochromatosis gene (HFE), which may be a marker of hereditary haemochromatosis, also has an influence on the course of PCT. Novel proteins and mechanisms influencing the absorption, transfer, storage and excretion of iron have been discovered in the last years. The key position in this field belongs to hepcidin, which influences the regulation of iron homeostasis and enables an early diagnosis of PCT. All cases of PCT should be thoroughly examined with special attention to coexistent risk factors of developing hepatic cirrhosis and/or primary hepatic carcinoma.